Calcium/Calmodulin Kinase IV Controls the Function of Both T Cells and Kidney Resident Cells - Ferretti, Andrew P.; Bhargava, Rhea; Dahan, Shani; Tsokos, Maria G.; Tsokos, George C. (Frontiers in Immunology, 2018)
Calcium calmodulin kinase IV (CaMK4) regulates multiple processes that significantly contribute to the lupus-related pathology by controlling the production of IL-2 and IL-17 by T cells, the proliferation of mesangial cells, and the function and structure of podocytes. CaMK4 is also upregulated in podocytes from patients with focal segmental glomerulosclerosis (FSGS). In both immune and non-immune podocytopathies, CaMK4 disrupts and structure and function of podocytes. In lupus-prone mice, targeted delivery of a CaMK4 inhibitor to CD4+ T cells suppress both autoimmunity and the development of nephritis. Targeted delivery though to podocytes averts the deposition of immune complexes without affecting autoimmunity in lupus-prone mice and averts pathology induced by adriamycin in normal mice. Therefore, targeted delivery of a CaMK4 inhibitor to podocytes holds high therapeutic promise for both immune (lupus nephritis) and non-immune (FSGS) podocytopathies.